2020
DOI: 10.1177/2325967120962869
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Shoulder and Knee Physical Examination

Abstract: The COVID-19 crisis has forced a sudden and dramatic shift in the way that clinicians interact with their patients, from outpatient encounters to telehealth visits utilizing a variety of internet-based videoconferencing applications. Although many aspects of pre–COVID-19 outpatient sports medicine care will ultimately resume, it is likely that telehealth will persist because of its practicality and because of patient demand for access to efficient and convenient health care. Physical examination is widely cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 80 publications
(158 reference statements)
2
43
0
2
Order By: Relevance
“…The examination quality could be increased by handing out a checklist to the patients in advance with preparatory information for the telemedicine consultation (22). Although in the presented study OTC have demonstrated limitations in terms of functional tests of a joint with classic examination methods, it seems that with the help of modi cations to those functional tests and the use of assistive devices, it is possible to make reliable statements about this important component of the examination (21,22). Most importantly, analyzing the established procedures in for each case individually, showed that the OTC recommendations for further treatment were similar to the live consultation recommendations in 96% of the cases.…”
Section: Discussionmentioning
confidence: 84%
“…The examination quality could be increased by handing out a checklist to the patients in advance with preparatory information for the telemedicine consultation (22). Although in the presented study OTC have demonstrated limitations in terms of functional tests of a joint with classic examination methods, it seems that with the help of modi cations to those functional tests and the use of assistive devices, it is possible to make reliable statements about this important component of the examination (21,22). Most importantly, analyzing the established procedures in for each case individually, showed that the OTC recommendations for further treatment were similar to the live consultation recommendations in 96% of the cases.…”
Section: Discussionmentioning
confidence: 84%
“…(f) O’Brien (active compression) test with the thumb pointed down and resistance provided by soup cans in grocery bag ( Supplemental Table 7 ). (g) O’Brien test with thumb pointed up [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The author(s) declared the following potential conflicts of interest with respect to the research, authorship, and/or publication of this article: Sridhar Pinnamaneni, MD; Joseph D. Lamplot Table 7). (g) O'Brien test with thumb pointed up [24].…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have divided the knee examination into a basic examination (core knee examination) and pathology-specific special testing [ 17 ]. The basic examination includes inspection, palpation, range of motion testing, motor testing, sensory testing, and a peripheral vascular examination [ 3 ].…”
Section: Preparation For Telemedicine Visitmentioning
confidence: 99%